Fluorine‐18 fluorodeoxyglucose positron emission tomography‐computed tomography for staging of canine insulinoma: 3 cases (2019–2020). (22nd November 2021) - Walczak, R.; Kawalilak, L.; Griffin, L.
Abstract : Objectives: Canine insulinomas are uncommon malignant functional pancreatic neuroendocrine tumours with a high metastatic rate. Diagnostic imaging aids with staging and surgical planning of these tumours; however, identification is unpredictable across modalities. High‐grade human pancreatic neuroendocrine tumours display increased avidity on 18 F‐fluorodeoxyglucose positron emission tomography‐CT. Materials and Methods: Dogs with clinicopathologic findings consistent with pancreatic insulinoma were prospectively enrolled. Patients underwent 18 F‐fluorodeoxyglucose positron emission tomography‐CT and CT angiography, followed by exploratory laparotomy. Results: Three patients met the inclusion criteria and had histologically confirmed insulinomas. Both metastatic lesions in patient 1 were mildly avid (SUVmax 2.79 and 3.01). In patient 2, the primary pancreatic insulinoma was minimally avid (SUVmax 2.16). The primary pancreatic lesion in patient 3 had similar avidity to normal pancreatic parenchyma (SUVmax 1.54) and was undetected on 18 F‐fluorodeoxyglucose positron emission tomography‐CT. Insulinomas demonstrated variable attenuation and contrast enhancement patterns on CT angiography and certain lesions were more conspicuous than on 18 F‐fluorodeoxyglucose positron emission tomography‐CT. Two metastatic lesions not visible on either imaging modality were discovered in patient 2 at surgery. Clinical Significance: Canine insulinomas were inconsistently avid on 18 F‐fluorodeoxyglucose positron emission tomography‐CT. This finding is likely attributable to the confounding clinicopathological features and multifaceted transformation of these tumours, in addition to the influence of variable tumour size, composition and vascularity. Unpredictable tumoural avidity limits the value of 18 F‐fluorodeoxyglucose positron emission tomography‐CT for staging canine insulinomas.